Post-elimination surveillance in formerly onchocerciasis endemic focus in Southern Mexico - Fernández-Santos, Nadia A.; Unnasch, Thomas R.; Rodríguez-Luna, Isabel C.; Prado-Velasco, Francisco Gibert; Adeniran, Adebiyi A.; Martínez-Montoya, Humberto; Rodríguez-Pérez, Mario A. (PLOS Neglected Tropical Diseases, 2020)
Author summary Elimination of transmission of onchocerciasis from Mexico was officially declared in 2015. In the present study, we report post-elimination surveillance (PES) in a formerly onchocerciasis endemic focus in Southern Mexico. From 2016 to the present, PES based on examination for suspected onchocercomas and parasitological studies were performed that together indicate that transmission of O. volvulus no longer exists in this former focus. This study supports the conclusion that onchocerciasis has been eliminated from Mexico.